Gynecologic cancer screening and communication with health care providers in women with Lynch syndrome. (27th August 2013) - Burton‐Chase, A.M.; Hovick, S.R.; Sun, C.C.; Boyd‐Rogers, S.; Lynch, P.M.; Lu, K.H.; Peterson, S.K.
Abstract We evaluated knowledge of gynecologic cancer screening recommendations, screening behaviors, and communication with providers among women with Lynch syndrome (LS). Women aged ≥25 years who were at risk for LS‐associated cancers completed a semi‐structured interview and a questionnaire. Of 74 participants (mean age 40 years), 61% knew the appropriate age to begin screening, 75–80% correctly identified the recommended screening frequency, and 84% reported no previous screening endometrial biopsy. Women initiated discussions with their providers about their LS cancer risks, but many used nonspecific terms or relied on family history. Most were not offered high‐risk screening options. While many women were aware of risk‐appropriate LS screening guidelines, adherence was suboptimal. Improving communication between women and their providers regarding LS‐related gynecologic cancer risk and screening options may help improve adherence.